Analgesic Efficacy Of Preoperative Versus Postoperative Ultrasound-Guided Transverse Abdominis Plane Block For Laparoscopic Cholecystectomy - Palijo, Muhammad Khalid; Feroze, Faheem; Faheem, Muhammad Shaheed Bin; Faheem, Saadia; Khalid, Maliha; Farooq, Saeed (Journal of Rawalpindi Medical College, 2025)
Objective: In enhanced recovery procedures, the transversus abdominis plane (TAP) block is applied as one of the multimodal pain control techniques. The study evaluated whether administering an ultrasound-guided TAP block before or after laparoscopic cholecystectomy is more effective for managing postoperative pain within enhanced recovery protocols. Methods: A prospective study was conducted at PAF Hospital Mushaf Sargodha between July 2024 and December 2024. Patients who met the criteria for laparoscopic cholecystectomy were split randomly into two groups (n=50 for each group). Patients in the preoperative group (PG) had a bilateral ultrasound-guided transversus abdominis plane block performed with 20 cc of bupivacaine 0.25% performed on them after the induction of general anaesthesia. A visual analogue scale was used to evaluate the patients’ levels of pain when they were first brought into the recovery room, as well as after four, eight, twelve, and twenty-four hours had passed. The pain score recorded in the recovery room as well as at the 4th, 8th, 12th, and 24th hours is the primary outcome. Result: The ultrasound-guided TAP block resulted in a significantly reduced pain score in the POG group in comparison to the PG group with stable hemodynamic parameters (heart rate and mean arterial pressure). Following the operation, the POG patients reported significantly less pain when coughing at 4,8,12 and 24 hours. The POG consistently had considerably higher levels of patient satisfaction across the board. Patients in the POG had much lower rates of post-operative nausea and vomiting and required a longer time duration before rescuing analgesic demand than patients in the PG group. Conclusion: When it comes to giving postoperative analgesia, our study suggested that postoperative TAP block is more effective than preoperative TAP block. Keywords: analgesic, ultrasound, Laparoscopic cholecystectomy